2(x-y) = 8 when x = 6

2(6-y) = 8

(2 x 6)+ (2 x -y) = 8

12 -2y = 8

12 -2y + 2y = 8 + 2y ..... Add 2y to both sides.

12 = 8 + 2y

12 - 8 = 8 - 8 + 2y ..... Subtract 8 from both sides

4 = 2y

4/2 = (2y)/2 ..... Divide both sides by 2

If you substitute the value for x (6) and the value for y (2) into the original equation, is it true?

2(x-y) = 8

2(6-2)

2(4)

8 = 8 .... Equation is true, the value for Y is correct when X = 6

I hope this helps

**Step 1**substitute 6 for the value of x in the equation2(6-y) = 8

**Step 2**Tidy this equation up now(2 x 6)+ (2 x -y) = 8

12 -2y = 8

**Step 3**Solve for y12 -2y + 2y = 8 + 2y ..... Add 2y to both sides.

12 = 8 + 2y

12 - 8 = 8 - 8 + 2y ..... Subtract 8 from both sides

4 = 2y

4/2 = (2y)/2 ..... Divide both sides by 2

**2 = y****Always check your answer!**If you substitute the value for x (6) and the value for y (2) into the original equation, is it true?

2(x-y) = 8

2(6-2)

2(4)

8 = 8 .... Equation is true, the value for Y is correct when X = 6

I hope this helps